Development of an Integrated Innovative Management Model for Enhancing Screening and Culturally Tailored Health Literacy among Liver Fluke and Cholangiocarcinoma High-risk Groups - Busba Buapan; Wilawan Pakwiset; Amornphan Tubtimdee; Pradit Sirison; Nuttapong Thakraiklang (Srinagarind Medical Journal, 2026)
Background and objectives: Cholangiocarcinoma (CCA) remains a critical emerging public health challenge, with Thailand reporting the highest problem globally. This study aimed to investigate existing problems and needs, develop and implement an integrated management model, and evaluate its effectiveness in enhancing screening efficiency and culturally tailored health literacy. Methods: This study employed a research and development (R&D) design, conducted in four phases. In Phase 1, the sample consisted of 500 at-risk individuals aged 15 years and older. Phase 2 involved 12 administrators and relevant stakeholders, along with 9 experts who validated the proposed model. Phase 3 included 120 research participants and 12,697 at-risk individuals aged 15 and above who underwent screening. Finally, Phase 4 involved 9 experts for the final quality evaluation of the model. Data were collected using questionnaires, focus group interview guides, performance records, and standardized assessment forms. Data analysis was performed using descriptive statistics, content analysis Z-test and, Wilcoxon signed rank test. Statistical significance was set at a 95% confidence interval (p < .05). Results: The study results are as follows: 1) Situational Analysis: Findings revealed a critical disconnect between state policies and the sociocultural realities of local communities, where the traditional consumption of raw fish persists. Additional barrier included delayed access to screening systems, a lack of effective inter-agency coordination, and the failure of conventional health communication strategies to trigger authentic, subconscious behavioral shifts. 2) Integrated Innovative Management Model: The developed model comprises four primary strategic activities: (1) Analysis of localized behaviors and cultural values; (2) Implementation of a screening management system spearheaded by Village Health Volunteers (VHVs); (3) Targeted behavioral modification interventions; and (4) Utilization of information technology for individualized health monitoring and follow-up. 3) Effectiveness of the Screening and Referral System: The screening identified suspected Cholangiocarcinoma (CCA) cases at a rate of 0.90%. Following the intervention, the target group exhibited significantly higher median scores in health literacy, awareness, and health-related behaviors compared to the pre-intervention period, with a moderate effect size, and 4) Lessons Learned and Model Validation: The synthesis of the model’s implementation underscored its core principles, primary objectives, operational processes, evaluation frameworks, and critical success factors for scalability. The finalized model was rigorously validated, demonstrating a high level of overall appropriateness and accuracy (μ= 4.49, σ = 0.25). Conclusion: The developed integrated health innovation significantly improved screening participation and health literacy among high-risk groups. Relevant authorities should consider scaling this model to other endemic areas.